Strategi Guru Sekolah Dasar pada Pembelajaran Bahasa Indonesia Berbantuan Teknologi - Rohmah, Inas Husnur; Rismawati, Rina; Julianto, Indra Rasyid (Cahaya Smart Nusantara, 2025)
Indonesian language learning has an important role in improving students' language skills, which include aspects of listening, reading, writing, and speaking. However, various challenges in its implementation, such as low student interest in learning and lack of innovation in teaching methods, are still the main obstacles. Along with the development of technology, the utilisation of digital media in learning is increasingly relevant to increase the effectiveness and motivation of students' learning. This research uses a descriptive qualitative method with a literature study approach to analyse the use of technology in Indonesian language learning in primary schools. The results show that the integration of technology, such as interactive learning media, educational applications, and project-based methods, can increase student participation and learning effectiveness. Teachers have a crucial role in adapting and optimising technology to suit students' needs. Therefore, innovative and varied strategies are needed to improve students' language skills in a more interesting and effective way.